Relationship of left ventricular, elastic and muscular arteries remodeling in patients with uncontrolled arterial hypertension - S. Ya. Dotsenko; V. G. Deynega; N. Ya. Dotsenko (Patologìâ)
Introduction. Uncontrolled hypertension is observed in 65-92% of hypertensive patients. It plays an important role in the development of adverse cardiovascular events and survival, which depend on subclinical target organ damage. There are reports on the relationship between ineffective hypertension control and left ventricular (LV) hypertrophy or large arteries stiffness. However, the nature of the remodeling in uncontrolled hypertension remains poorly understood.